PENGARUH STATUS SOSIAL EKONOMI ORANG TUA, DISIPLIN DAN MOTIVASI BELAJAR SISWA TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN SISWA SMK PUTRA HARAPAN PLEMAHAN TAHUN PELAJARAN 2019/2020 - Monika, Suci; Sugiono, Sugiono; Subagyo, Subagyo (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to determine the effect of parents' socioeconomic status, learning discipline, learning motivation on learning outcomes in Creative Products and Entrepreneurship subjects at SMK Putra Harapan in the 2019/2020 school year. This research is a type of correlation research that is used to determine the causal relationship between variable X and variable Y. The population in this study were 156 respondents of class XI SMK Putra Harapan with a sample of 30 respondents taken by simple random sampling technique. Data collection techniques using questionnaires and observation sheets. Furthermore, the data were analyzed using multiple linear regression analysis techniques. The results showed that: (1) there was a significant positive effect between parents' socioeconomic status on learning outcomes, (2) there was a significant positive effect between learning disciplines, (3) there was no significant influence between motivation on learning outcomes.